Bacterial mechanosensitive channels: Models for studying mechanosensory transduction - Martinac, B.; Nomura, T.; Chi, G.; Petrov, E.; Rohde, P.; Battle, A.; Foo, A.; Constantine, M.; Rothnagel, R.; Carne, S.; Deplazes, Evelyne; Cornell, B.; et al. (Mary Ann Liebert, Inc. Publishers, 2014)
Significance: Sensations of touch and hearing are manifestations of mechanical contact and air pressure acting on touch receptors and hair cells of the inner ear, respectively. In bacteria, osmotic pressure exerts a significant mechanical force on their cellular membrane. Bacteria have evolved mechanosensitive (MS) channels to cope with excessive turgor pressure resulting from a hypo-osmotic shock. MS channel opening allows the expulsion of osmolytes and water, thereby restoring normal cellular turgor and preventing cell lysis. Recent Advances: As biological force-sensing systems, MS channels have been identified as the best examples of membrane proteins coupling molecular dynamics to cellular mechanics. The bacterial MS channel of large conductance (MscL) and MS channel of small conductance (MscS) have been subjected to extensive biophysical, biochemical, genetic, and structural analyses. These studies have established MscL and MscS as model systems for mechanosensory transduction. Critical Issues: In recent years, MS ion channels in mammalian cells have moved into focus of mechanotransduction research, accompanied by an increased awareness of the role they may play in the pathophysiology of diseases, including cardiac hypertrophy, muscular dystrophy, or Xerocytosis. Future Directions: A recent exciting development includes the molecular identification of Piezo proteins, which function as nonselective cation channels in mechanosensory transduction associated with senses of touch and pain. Since research on Piezo channels is very young, applying lessons learned from studies of bacterial MS channels to establishing the mechanism by which the Piezo channels are mechanically activated remains one of the future challenges toward a better understanding of the role that MS channels play in mechanobiology.